Clinical utility of plasma cell-free DNA in pancreatic neuroendocrine neoplasms - Cowzer, Darren; Shah, Ronak H; Chou, Joanne F; Kundra, Ritika; Punn, Sippy; Fiedler, Laura; DeMore, April; Capanu, Marinela; Berger, Michael F; Reidy-Lagunes, Diane; Raj, Nitya (Endocrine-related cancer, 2024)
In advanced pancreatic neuroendocrine neoplasms (PanNEN), there are little data detailing the frequency of genetic alterations identified in cell free DNA (cfDNA), plasma-tissue concordance of detected alterations, and clinical utility of cfDNA. Patients with metastatic PanNENs underwent cfDNA collection in routine practice. Next-generation sequencing (NGS) of cfDNA and matched tissue when available was performed. Clinical actionability of variants was annotated by OncoKB. Thirty-two cfDNA samples were analyzed from 25 patients, the majority who had well-differentiated intermediate grade disease (13/25; 52%). Genomic alterations were detected in 68% of patients and in 66% of all cfDNA samples. The most frequently altered genes were DAXX (28%), TSC2 (24%), MEN1 (24%), ARID1B (20%), ARID1A (12%), and ATRX (12%). Twenty-three out of 25 (92%) patients underwent tumor tissue NGS. Tissue-plasma concordance for select genes was as follows:DAXX (95.7%), ARID1A (91.1%), ATRX (87%), TSC2 (82.6%), MEN1 (69.6%). Potentially actionable alterations were identified in cfDNA of 8 patients, including TSC2 (4; level 3b), ATM (1; level 3b), ARID1A (2; level 4), and KRAS (1; level 4). An ETV6:NTRK fusion detected in tumor tissue was treated with larotrectinib; at progression, sequencing of cfDNA identified an NTRK3 G623R alteration as the acquired mechanism of resistance; the patient enrolled in a clinical trial of a second-generation TRK inhibitor with clinical benefit. In metastatic PanNENs, cfDNA-based NGS identified tumor-associated mutations in 66% of plasma samples with a high level of plasma-tissue agreement in PanNEN-associated genes. Clonal evolution, actionable alterations, and resistance mechanisms were detected through circulating cfDNA genotyping.